Comparison of Metabolome and Transcriptome of Flavonoid Biosynthesis in Two Colors of Coreopsis tinctoria Nutt. - Jiang, Hong; Li, Zhiyuan; Jiang, Xiumei; Qin, Yong (Frontiers in Plant Science, 2022)
Coreopsis tinctoria Nutt. (C. tinctoria) has a long history of application and high economic and medicinal value. Flavonoids, the main active components of C. tinctoria, are widely studied in pharmacology and food development. However, the flavonoid biosynthesis pathway in C. tinctoria is unclear. In this study, we comprehensively compared the transcriptomes and metabolite profiles of two colors of C. tinctoria flowers (LS and JS) at different flowering stages. A total of 165 flavonoids (46 flavonoids, 42 flavonols, 22 anthocyanins, 18 chalcones, 12 dihydroflavonols, 9 isoflavones, 8 dihydroflavonoids, 6 flavanols, and 2 tannins) were identified in LS and JS at different flowering stages. Thirty-three metabolites (11 anthocyanins, 11 flavonols, 7 flavonoids, 2 dihydroflavonols, 1 dihydroflavone, and 1 chalcone) were found to be statistically significantly different in the LS vs. JS groups. LS flowers accumulated higher levels of 10 anthocyanins (7 cyanidins and 3 pelargonidins) than JS flowers. Furthermore, candidate genes related to the regulation of flavonoid and anthocyanin synthesis were identified and included 28 structural genes (especially F3H, Cluster-28756.299649, and 3GT, Cluster-28756.230942) in LS and JS, 6 key differentially expressed transcription factors (especially MYB90a, Cluster-28756.143139) in LS and JS, and 17 other regulators (mainly including transporter proteins and others) in LS. Our results provide valuable information for further studies on the mechanism underlying flavonoid biosynthesis in C. tinctoria.